Dysregulated iron homeostasis is strongly associated with multiorgan failure and early mortality in acute‐on‐chronic liver failure. Issue 4 (10th March 2015) - Maras, Jaswinder Singh; Maiwall, Rakhi; Harsha, H.C.; Das, Sukanta; Hussain, Md.Shabir; Kumar, Chandan; Bihari, Chhagan; Rastogi, Archana; Kumar, Manoj; Trehanpati, Nirupama; Sharma, Shvetank; Pandey, Akhilesh; et al.
Abstract : Acute‐on‐chronic liver failure (ACLF) is an ailment with high incidence of multiorgan failure (MOF) and consequent mortality. Dysregulated iron homeostasis and macrophage dysfunction are linked to increased incidence of MOF. We investigated whether a panel of circulating iron‐regulating proteins are associated with development of MOF and can predict 15‐ or 30‐day mortality in ACLF patients. One hundred twenty patients with ACLF, 20 patients with compensated cirrhosis, and 20 healthy controls were studied. Relative protein expression profiling was performed in the derivative cohort and confirmed in the validation cohort. A panel of iron regulators and indices were determined. Multiparametric flow cytometry for quantitation of labile iron pool (LIP) was performed. Validation studies confirmed lower serum transferrin (Tf) and ceruloplasmin levels in ACLF and ACLF‐MOF, compared to patients with cirrhosis and controls ( P < 0.01). Serum iron and ferritin levels were markedly elevated ( P < 0.001; P < 0.05) and hepcidin levels were lower ( P < 0.001) in ACLF patients with MOF than those without and other groups ( P < 0.001). Percentage Tf saturation (%SAT) was higher in ACLF‐MOF (39.2%; P < 0.001) and correlated with poor outcome (hazard ratio: 6.970; P < 0.01). Intracellular LIP indices were significantly elevated in the subsets of circulating macrophages in ACLF‐MOF, compared to other groups ( P < 0.01). Whereas expression of iron‐regulatory genes was markedly down‐regulated, genes related to endoplasmic reticulum stress, apoptosis, and inflammation were up‐regulated in ACLF patients, compared to patients with cirrhosis. Severe dysregulation of autophagy mechanisms was also observed in the former. Conclusions : Iron metabolism and transport are severely deranged in ACLF patients and more so in those with MOF. %SAT, circulating hepcidin, and LIP in macrophages correlate with disease severity and %SAT could be used for early prognostication in ACLF patients. (Hepatology 2015;61:1306–1320)